Ethnicity, Voter Alignment and Political Party Affiliation – an African Case: Zambia - Gero Erdmann (German Institute of Global and Area Studies (GIGA), 2007)
Conventional wisdom holds that ethnicity provides the social cleavage for voting behav-iour and party affiliation in Africa. Because this is usually inferred from aggregate data of national election results, it might prove to be an ecological fallacy. The evidence based on individual data from an opinion survey in Zambia suggests that ethnicity matters for voter alignment and even more so for party affiliation, but it is certainly not the only factor. The analysis also points to a number of qualifications which are partly methodology-related. One is that the degree of ethnic voting can differ from one ethno-political group to the other depending on various degrees of ethnic mobilisation. Another is that if smaller eth-nic groups or subgroups do not identify with one particular party, it is difficult to find a significant statistical correlation between party affiliation and ethnicity - but that does not prove that they do not affiliate along ethnic lines. – – Wahlverhalten und Mitgliedschaft in politischen Parteien Afrikas ist nur wenig untersucht worden. Gewöhnlich wird argumentiert, dass Ethnizität als soziale Konfliktlinie das Wahlverhalten und die Parteienmitgliedschaft strukturiert. Da dieses Argument auf hoch aggregierten Wahldaten beruht, kann hier ein ökologischer Fehlschuss vorliegen. Die vorliegende Analyse beruht deshalb auf individuellen Umfragedaten aus Sambia. Das Ergebnis ist, dass Ethnizität tatsächlich eine Rolle für das Wahlverhalten und die Parteienmitgliedschaft spielt, aber keineswegs den einzigen Erklärungsfaktor darstellt. Die Analyse offenbart zudem eine Reihe von Einschränkungen und Qualifizierungen, die teilweise methodischer Natur sind. Eine ist, dass ethnisches Wahlverhalten und Parteienmitgliedschaft von einer ethnischen Gruppe zur anderen unterschiedlich ist, dass, wenn sich kleinere ethnische Gruppen oder Untergruppen mit keiner Partei identifizieren, es schwierig wird, statistisch signifikante Korrelationen zu finden - was indessen noch nicht beweist, dass Ethnizität keine Rolle spielt.
Keywords: 300; social cleavages; ethnicity; voting behaviour; political party identification; political party affiliation; Zambia